Performance of Radiator with Various Coolant Flow Rate - arif surono surono (Suara Teknik : Jurnal Ilmiah, 2021)
This research aims to evaluate the effect of fluid flow rate on the effectiveness of radiator performance by using coolant. The research began by making a series of test kits consisting of radiators, flowmeters, pumps, pipes, heaters and coolant reservoirs. The data collection of research was carried out at the temperature of the entrance, wall and exit of the radiator. In this study we did variations in fluid flow speed of 2.5, 4.5, and 6 LPM. The results of the study were able to lower the temperature at the use of fluid flow rate 6 LPM able to dissipate heat into the environment well. The temperature decrease occurred by 2.5%. Meanwhile, the lowest average radiator effectiveness value at the lowest speed at 6 LPM was 0.905 highest at a fluid flow rate of 4.5 of 0.930.